Pengaruh Kondisi Tanah Terhadap Kerusakan Dengan Menggunakan Metode Road Condition Index (RCI) Pada Ruas Jalan Pronoyudo Kecamatan Junrejo-Kota Batu - Muhammad Sadillah; Andy Kristafi Arifianto; Deojinda A. M. Amaral (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
Subgrade with poor strength and stability would cause the pavement to deform and crack easily. Different locations have different subgrade conditions. Different soil characteristics in different locations call for different treatment or stabilization measures. Poor subgrade strength is observed in Pronoyudo Street in Junrejo Sub-District, Batu City. This is evidenced by the cracked and chipped asphalt surface. The method used to determine the type and level of road damage in the study was Road Condition Index (RCI), while subgrade strength or CBR (California Bearing Ratio) was determined using DCP. In addition, sieve analysis was also performed for foundation material as well as testing water content and subgrade plasticity. Observations were made along 1,000 m (1 km) which was divided into 200 sq m. The analysis results showed a mean Road Condition Index (RCI) of 6.96% and the mean CBR value using the DCP tool was 2.48% (< 5%) with a DDT value of 3.39. A routine or periodic maintenance program is deemed to be the right management method for Pronoyudo Street in Junrejo Sub-District in Batu City. Therefore, overall, the program that has been carried out for road maintenance is in accordance with the results of research analysis and Public Works Ministerial Decree No. 13/PRT/M/2011.